The role of Dentin Sialophosphoprotein (DSPP) in craniofacial development - Carlos Alberto Figueredo; Nancy Abdelhay; Seema Ganatra; Monica Prasad Gibson (Elsevier, 2022)
DSPP is known to be important in the formation of dentin. In DSPP's absence, a severely hypomineralized dentin is formed, in a condition known as dentinogenesis imperfecta (DGI). DSPP has recently been found in several different tissues, including the mandibular condylar cartilage and craniofacial skeleton. However, there is limited literature on the role of DSPP in these tissues. Therefore, the objective of the present study was to investigate the role of DSPP in craniofacial development.Two mice strains, DSPP knockout and C57BL/6J wild type, were compared at 1, 3, and 6-months of age. Skulls and condyles were investigated through morphological and histological analyses. Cell culture was also conducted to investigate the potential effects of DSPP absence in osteoblasts from the calvaria.Mineralization defects were noticed in the structures of skulls and MCC, with the most significant impact at 1 month of age. Therefore, DSPP is an essential protein for the normal mineralization of craniofacial tissues.